RE-INTERPRETASI DAN RE-ORIENTASI PENDIDIKAN INKLUSIF - Herawati, Nenden Ineu (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2018)
Abstract: The understanding of inclusive education is still inaccurate, so the interpretation and orientation towards that implementation are not appropriate as it should be. Nowadays, be found in the field that term of inclusive education is only limited to children with special needs learned together with general children in regular schools. Whereas, the term of inclusive education refer to provide the possible opportunity or access widely for all children in order to obtain the quality of education and in accordance with the needs without discrimination. Therefore, schools that enroll in inclusive education are required to adjust in terms of curriculum, facilities, the infrastructure of education, and learning systems as well that adjusted with the needs of children with special needs. In the other hand, children with special needs are those with temporary or permanent special needs that require more intense educational services. If children are required to receive an education service that is appropriate to their needs and existence through an inclusive education program, it will provide the possible opportunity widely for all children with special needs to get a proper education according to their needs. Moreover, it can create an education system that respects to diversity, non-discrimination and friendly in learning. Thus, it can implement the mandate of the Constitution of 1945, article 31, paragraph 1, Law of 2003 No. 20 regarding National Education System on article 5, paragraph 1, and Law of 2002 No 23 regarding The Right and Protection of Children in article 51. Abstrak: Pemahaman terhadap pendidikan Inklusif masih belum tepat, sehingga in terpretasi dan o-rientasi pelaksanaannya pun belum sesuai sebagaimana seharusnya yang sekarang dijumpai di lapangan bahwa yang dinamakan pendidikan inklusif adalah hanya sebatas anak kebutuhan khusus belajar bersama-sama dengan anak-anak normal di sekolah reguler.Padahal yang dinamakan pendidikan inklusif adalah memberikan kesempatan atau akses yang seluas-luasnya kepada semua anak untuk memperoleh pendidikan yang bermutu dan sesuai dengan kebutuhan tanpa diskriminasi, oleh karena itu sekolah yang menyeleggarakan pendidikan inklusif dituntut harus menyesuaikan baik dari segi kurikulum, sarana dan prasarana pendidikan maupun sistem pembelajaran yang sesuai dengan kebutuhan individu peserta didik yang berkebutuhan khusus. Sedangkan yang dimaksud dengan anak berkebutuhan khusus adalah mereka yang memiliki kebutuhan khusus sementara atau permanen yang membutuhkan pelayanan pendidikan yang lebih intens. Jika anak berkebutuhan mendapat layanan pendidikan yang sesuai dengan kebutuhan dan keberadaannya melalui program pemdidikan inklusif, maka akan memberikan kesempatan seluas-luasnya kepada semua anak berkebutuhan khusus mendapatkan pendidikan yang layak sesuai dengan kebutuhannya. Serta dapat menciptakan sistem pendidikan yang menghargai keanekaragaman, tidak diskriminasi serta ramah terhadap pembelajaran sehingga dapat mengamalkan amanat Undang-Undang-Undang 1945 pasal 31 ayat 1 juga undang-undang No 20 tahun 2003 tentang system pendidikan Nasional pasal 5 ayat 1 dan Undang-Undang no 23 tahun 2002 tentang hak dan perlindungan anak pasal 51.